Environmental Empowerment through the use of Plastic Waste in Growing the Creative and Innovative Soul of Pembinaan Kesejahteraan Keluarga (PKK) of Women - Ahmad Fauzi; Ahmad Hisam Bintoro; Ahmad Bustomi; Arif Hidayat; Erwin Setiawan; Elza Fauziah Shihab; Anggeta Purnama; Fadhilah Nur S; Evita Dwi Lestari; Lutviatun Nikmah; Ani Nour Azizah; Mardliyana Ifadah; Muhammad Nur Amin (Yayasan Payungi Smart Madani, 2024)
Plastic waste management is the main focus of community service in Tanjung Harapan village, Seputih Banyak sub-district, Central Lampung. Plastic waste is identified as a crucial problem with significant negative impacts on the environment. The aim of this service is to gain an understanding of the concept of plastic waste management, creating a clean environment and providing a positive impact on local residents. Through the 3R concept (Reuse, Reduce and Recycle), this service aims to reduce plastic waste in the village. Using the CBPR (Community Based Participatory Research) method which is a mixed method for researching community aspirations and needs. Participants in this activity were 15 PKK women from Tanjung Harapan village. This activity was held at the Tanjung Harapan Seputih Banyak Village Meeting Hall. The results of this service show that PKK women as activity participants increasingly understand how to manage plastic waste. The conclusion of this activity had a positive impact on PKK women because they were given strengthened insight into how to manage plastic waste.